(The determination of The Composition of Kapol Oil (Ammomum cardammomum) and Its Comparison with Kapolaga Oil (Elettaria cardammomum) by GLC Analysis - Achmad Moestafa; Sumarsi - (Balai Besar Industri Agro, 1993)
Kapol and kapolaga are the local name in indonesia for cardamom.Although their botanical name has already clear for each species,nevertheless there were stil some confusions in regional name.Some people call it kapol for kapolaga on in turn kapolaga was called kapol. An attempt tom distinguish which is which a GLC analysis on their essential oils were determined.From the result it distinctly can be recognised due to their GLC finger print didi not match each other so their composition were not the same. Kapol oil was totally different from kapolaga oil since its main component was 1,8-cineol,while kapolaga oil contained 1,8-cineol,terpinil acetate and geralsacetate at its main component.According to perseglove (1981)the first was belong to ammomum cardamomum and the latter was belong to Elletaria cardamomum.Since the letter type was more popular and reqodnised in international market,the first type was called as false cardamon. This is no fair since every type of cardamun had their own application and market.The result of this study willbe used as data to support the international standartd organitation (ISO) proposal.